Influence of 4-vinylbenzylation on the rheological and swelling properties of photo-activated collagen hydrogels. Issue 8 (2016) - Tronci, Giuseppe; Grant, Colin A.; Thomson, Neil H.; Russell, Stephen J.; Wood, David J.
ABSTRACT: Covalent functionalisation of collagen has been shown to be a promising strategy to adjust the mechanical properties of highly swollen collagen hydrogels. At the same time, secondary interactions between for example, amino acidic terminations or introduced functional groups also play an important role and are often challenging to predict and control. To explore this challenge, 4-vinylbenzyl chloride (4VBC) and methacrylic anhydride (MA) were reacted with type I collagen, and the swelling and rheological properties of resulting photo-activated hydrogel systems investigated. 4VBC-based hydrogels showed significantly increased swelling ratio, in light of the lower degree of collagen functionalisation, with respect to methacrylated collagen networks, whilst rheological storage moduli were found to be comparable between the two systems. To explore the role of benzyl groups in the mechanical properties of the 4VBC-based collagen system, model chemical force microscopy (CFM) was carried out in aqueous environment with an aromatised probe against an aromatised gold-coated glass slide. A marked increase in adhesion force ( F : 0.11±0.01 nN) was measured between aromatised samples, compared to the adhesion force observed between the non-modified probe and a glass substrate ( F : 2.64±1.82 nN). These results suggest the formation of additional and reversible π-π stacking interactions in aromatic 4VBC-based networks and explain the remarkable rheological properties of this system in comparison to MA-based hydrogels.